Robust Tracking Control of Networked Control Systems: Application to a Networked DC Motor - Shi, Yang; Huang, Ji; Yu, Bo (IEEE transactions on industrial electronics (1982), 2013)
This paper investigates robust H 2 and H ∞ step tracking control methods for networked control systems subject to random time delays modeled by Markov chains. To make full use of the delay information, the proposed two-mode dependent output feedback controller depends on both sensor-to-controller and controller-to-actuator delays. To actively compensate for the controller-to-actuator delays, we propose the "send all, apply one" scheme: Sending a sequence of control signals, then at the actuator/plant node, applying the appropriate control signal according to the actual controller-to-actuator delay. Using the augmentation method, the resulting closed-loop system can be formulated as a discrete-time Markovian jump linear system. The H 2 and H ∞ step tracking problems are tackled by solving a set of linear matrix inequalities with nonconvex constraints. Both numerical simulations and experiments on a networked dc motor system are conducted to illustrate the effectiveness of the proposed methods.